1998
DOI: 10.1046/j.1365-2044.1998.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mivacurium pretreatment on intra‐ocular pressure changes induced by suxamethonium

Abstract: SummaryWe have evaluated the effects of the volume and speed of administration of local anaesthetic during peribulbar anaesthesia. One hundred and forty patients scheduled for cataract surgery were randomly allocated to one of four groups of 35. Each patient received an injection of the same mixture of lignocaine, bupivacaine and hyaluronidase. Patients in group A were given 9 ml at a speed of 5 ml.min À1 , group B were given the same volume at 12 ml.min À1 , group C were given 13.5 ml at 5 ml.min À1 and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The inference is that a decrease in systemic circulatory dynamics results in a decrease in aqueous humor production. Induction of anesthesia reportedly decreases IOP by 5-7 mmHg (20-40%) when compared with IOP prior to the induction of anesthesia [11][12][13][14] . The results of our study were also similar to the ndings of these reports.…”
Section: Discussionmentioning
confidence: 99%
“…The inference is that a decrease in systemic circulatory dynamics results in a decrease in aqueous humor production. Induction of anesthesia reportedly decreases IOP by 5-7 mmHg (20-40%) when compared with IOP prior to the induction of anesthesia [11][12][13][14] . The results of our study were also similar to the ndings of these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Chiu and colleagues reported that pretreatment with mivacurium prevented the increase in intra‐ocular pressure associated with the administration of suxamethonium [1]. Using a rapid‐sequence induction technique with alfentanil and propofol, the mean increase in intra‐ocular pressure was 0.4 mmHg in the mivacurium group versus 3.5 mmHg in the control group.…”
mentioning
confidence: 99%